2020
DOI: 10.1186/s12936-020-03376-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of artemether-lumefantrine for treating uncomplicated Plasmodium falciparum cases and molecular surveillance of drug resistance genes in Western Myanmar

Abstract: Background Currently, artemisinin-based combination therapy (ACT) is the first-line anti-malarial treatment in malaria-endemic areas. However, resistance in Plasmodium falciparum to artemisinin-based combinations emerging in the Greater Mekong Sub-region is a major problem hindering malaria elimination. To continuously monitor the potential spread of ACT-resistant parasites, this study assessed the efficacy of artemether-lumefantrine (AL) for falciparum malaria in wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Concurrent mutations were also identified in pfdhps . Frequencies of the mutations were similar to or slightly higher than those of P. falciparum collected from northern (Banmauk, Sagaing State and Laiza, Kachin State) and western (Paletwa, Chin State) Myanmar [ 25 , 34 ]. However, more diverse haplotypes of pfdhps were identified in P. falciparum isolates collected from Mandalay region.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Concurrent mutations were also identified in pfdhps . Frequencies of the mutations were similar to or slightly higher than those of P. falciparum collected from northern (Banmauk, Sagaing State and Laiza, Kachin State) and western (Paletwa, Chin State) Myanmar [ 25 , 34 ]. However, more diverse haplotypes of pfdhps were identified in P. falciparum isolates collected from Mandalay region.…”
Section: Discussionmentioning
confidence: 85%
“…In the case of pfdhfr , these mutations were commonly identified as concurrent mutations rather single mutations in the gene. Frequencies of quadruple mutation (AIRNL), triple mutation (AIRNI or ANRNL), and double mutation (ANRNI) were comparable to or slightly different from those of P. falciparum collected from northern (Banmauk, Sagaing State and Laiza, Kachin State) and western (Paletwa, Chin State) Myanmar [ 25 , 34 ]. Concurrent mutations were also identified in pfdhps .…”
Section: Discussionmentioning
confidence: 99%
“…However, no other African studies have demonstrated an increased therapeutic failure rate when these alleles are present [ 74 76 ]. In Asia, clinical failure rates have been linked to the increase in mdr1 copy number as compared to the mdr 86ASN alleles [ 77 ]. The increase in mdr1 copy number has rarely been reported in Africa [ 52 , 78 ], and this study did not observe any such increase.…”
Section: Discussionmentioning
confidence: 99%
“…163 In Northeast Myanmar, where the G6PD Mahidol variant is prevalent, we conducted an observational study in a cohort of 152 vivax patients to follow the risk of acute hemolysis 122 Laos, 192 Vietnam, 193 Thailand, 194,195 and Myanmar. 124,127,142 This figure appears in color at www.ajtmh.org.…”
Section: Antimalarial Drug Resistancementioning
confidence: 99%
“…Map of the GMS showing the prevalence and distribution of major PfK13 mutations as pie graphs above the malaria incidence heatmap of the region in 2020. The PfK13 mutation status was updated using malaria parasites collected primarily in 2016 from Cambodia,122 Laos,192 Vietnam,193 Thailand,194,195 and Myanmar 124,127,142. This figure appears in color at www.ajtmh.org.…”
mentioning
confidence: 99%